ART APPRECIATION FOR HIGH SCHOOL (Research Conducted at SMAN 5 and SMA Taruna Bakti Bandung) - PARAMITA, NORIE
appreciation. To understand the beauty, both the nature and the art, each individual, should experience artistic experiences in the process of art creation and gaining knowledge, understanding, and enjoyment of the arts. By having these experiences, students are enabled to sense the act of appreciation through perception, interpretation, creation, and reflection. The purpose of this study is to comprehend the process of art appreciation at high school program. The author wanted to understand the application of art learning art at schools, in which the main objectives are to comprehend students' cognitive and emotional abilities through experience and aesthetic understanding. This research uses theories that are relevant to the learning process in the arts, and the concept of appreciation. This research was conducted at SMAN 5 and Taruna Bakti High School by qualitative approach. The research was not intended to compare both schools, but the main objective was to describe the process of art appreciation in each school by doing an observation, interviews, and open questionnaires as research instruments. The results of the analysis showed that, in the process of learning art, students mainly gain (1) knowledge, materials and creative techniques in the making of the art, and (2) learned the concepts and theory of the arts by observation, and discussion, and making paper. The learning process showed a pattern of a manner of appreciation, as proposed by Osborne. There was a tendency that students appreciate art (1) through skill and (2) through perceptual awareness. From the observation, the tendency showed that students appreciate art by learning (1) through skills training, and (2) through perceptual awareness. Appreciation as skills has trained students to appreciate art through the complexity of techniques when creating the art. Whereas in appreciation as perception, students were more tended to appreciate art (1) by observation and capturing the quality of work, and (2) by understanding the concepts and meanings of the art through aesthetic experience.